DZIELIMY SIĘ DOŚWIADCZENIEMA rare cause of dyspnea and palpitations: mediastinal schwannoma - Tekin, Gulacan; Ozgel, Mehmet; Kenan Tekin, Yusuf; Erbay, Ali Rıza (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
A 65-year-old woman presented with worsening of respiratory discomfort and palpitations for two months. Echocardiography revealed a mediastinal mass compressing the left atrium which measured 61 × 47 mm. Computed tomography (CT) and magnetic resonance imaging (MRI) showed a well-circumscribed mass with hypointense septation located between the left atrium and descending aorta and adjacent to the esophagus. We report a very rare case of the left atrium compressing a mediastinal tumor which was a schwannoma.